Microeconomics with spreadsheets - Basov, Suren (Singapore World Scientific Publishing Co. Pte. Ltd., 2017)
Microeconomics with Spreadsheets starts with the mathematical preliminaries and covers consumer theory, producer theory, general equilibrium, game theory, market structure and economics of information--Provided by publisher.
PART 1 - Mathematical Preliminaries - Chapter 1 - Constraint Optimization - - Constraint optimization with equality constraints - - Constraint optimization with inequality constraints - - Introduction to Solver and using Solver to solve constraint optimization problems - - Some pitfalls of numerical optimization - - Envelope theorem for constraint optimization and the economic meaning of Lagrange multipliers - - Problems - PART 2 - Market Interactions - Chapter 2 - The Consumer Theory - - The formal statement of the consumer's problem - - Convex Preferences - - Properties of Demand - Marshallian demands for some commonly used utility functions - - Advanced topics in consumer theory: indirect utility and hicksian demand - - The Roy's Identity - - The dual problem -- Problems - Chapter 3 - The Producer Theory - - A neoclassical firm - - Cobb-Douglas producton function - - Constant Returns to Scale - - Production possibilities responsibilities frontier of an economy - - Marginal rate of technological transformation - - Hotelling Lemma - - ConditionaL Cost - - Problems - Chapter 4 - General Equilibrium - - The Robinson Crusoe's economy - - The pure exchange economy - - Role of prices in ensuring optimality of Walrasion allocation - - Using Excel to compute Walrasion equilibrium - - Problems - Chapter 5 - Choise and Uncertainty - - Expected Utility - - Shape of the Bernoulli utility and risk-aversion - - An example: buying insurance - - Stochastic dominance - - Problems - PART 3 - Strategic Interactions - Chapter 6 - Game Theory - - What is a game - - The normal form and the extensive form - - Mixed strategies and behavioral strategies - - Simultaneous-move games of complete information - - Dominant and dominated strategies - - Nash equilibrium - - Simultaneous-move games of incomplete information - - Harsanyi doctrine - - Dynamic games - - Subgames and SPNE - - Backward induction (BI) and CKR - - Some critique of the BI - - Weak Perfect Bayesian equlibrium (WPBE) - - Problems - Chapter 7 - Theory of Imperfect Competition and Industry Structure - - A competitive firm - - A monopoly - - Oligopoly - - Bertrand competition - - Cournot competition - - Stackelberg model of duopoly - - Problems - PART 4 - The Economics of Information - Chapter 8 - Hidden Information Models - - The adverse selection model - - The general signaling model - - The Spence model and economics of education - - The intuitive criterion - - The competitive screening model - - A screening model of education - - The insurance model - - The monopolistic screening model - -The monopolistic screening: the case of two types - - The monopolistic screening with two types: Excel implementation - - The monopolisitc screening: the case of continuum of types - - Problems - Chapter 9 - Hidden Action - - Non-monotonic incentive schemes - - Moral hazard in teams - - Problems - Chapter 10 - Introduction to Auctions - - Independent private values model - - Analysis of the four standard auctions - - A general incentive compatible mechanism - - Problems - Part 5 - Mathematical Appendix - Chapter 11 - The Formal Logic - - Basics - - Quantifiers - - Negated Statements - - Problems - Chapter 12 - Basics of Set Theory - - Basic operations with sets - - Convex Sets - - Problems - Chapter 13 - Solutions of Some Equations Systems of Simulataneous Equations - - Solving Linear Equations - - Quadratic equations - - Basics of matrix algebra and Cramer's rule - - Matrices - - Determinants and Cramer's rule - - Economic applications of systems of simultaneous equations - - Problems - Chapter 14 - Basics of Calculus - - Open and closed sets - - Continuous functions and compact sets - - Derivatives and differentiability - - Calculating derivatives - - The antiderivative and integral - - L'Hospital rule - - Second derivatives and local extrema - - More matrix algebra - - Envelope theorem for unconstraint optimization - - Continuous random variables - - Correspondences - - Problem.
Includes bibliographical references and index.
Keywords: Microeconomics